Kualitas Water Kefir Nanas (Ananas comosus) dengan Penggunaan Jenis Gula Berbeda - Luthfiyyah AD, Rahmi; Fitra Suzanti; Darmawati (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This research is motivated by public awareness of health and public concerns about calories and the dangers of diabetes from sweet foods and drinks. Therefore, it is necessary to develop functional foods that are rich in benefits and low in sugar such as pineapple water kefir using corn sugar or stevia sugar. This study aims to determine the quality of pineapple water kefir using cane sugar, corn sugar and stevia sugar in terms of lactic acid parameters, acidity level (pH) and organoleptic characteristics including color, aroma, taste, texture and level of preference (hedonic) of the water kefir produced. This study is included in the type of quantitative research with experimental methods. The results showed that the provision of different sugars did not significantly affect the levels of lactic acid and acidity level (pH) of pineapple water kefir. Organoleptic tests showed that panelists liked the most pineapple water kefir with stevia sugar (G3) which has the characteristics of a pale yellow color, a not too pungent aroma, a very sour taste and a slightly runny texture. Based on the results of these studies, it can be concluded that stevia sugar can be used as a substitute for cane sugar in making pineapple water kefir. Keywords: Water kefir, pineapple, cane sugar, corn sugar, stevia sugar